The Correlationship Of School Age Children Characteristics In Bullying Occurrence At Sd Negeri 2 Cot Girek, Aceh Utara Regency - Fatmawati; Dian Vita Sari (Jurnal Kesehatan Akimal, 2022)
Education is series efforts that made by individuals as a form of process in gaining experience to realizing a better life. The first education is basic education which is the initial foundation to improve personality development in the next direction. School is an ideal place to realize education, potential, and talent to children. But nowadays there is a lot of violence against children verbally or bullying. The purpose of this study was to determine the actual incidence of bullying that occurred in school-age children, especially elementary schools. This study aims to examine which the characteristics of school-age children are related to bullying occurence at state elementary school 2 in the village of Cot Girek, North Aceh Regency. This study is a descriptive design with a correlation study by using a cross sectional approach. The population of this study were all students of SD Negeri 2 Cot Girek as many as 270 people. The sampling technique in this study was carried out using purposive sampling technique. The correlation ship between Sex of School-Age Children and the Incidence of Bullying in SD Negeri 2 Cot Girek, North Aceh District, through the chi-square test results showed a p-value of 0.008 <0.05. So it can be concluded that there is a significant correlation between the sex of school-age children and the incidence of bullying at SD Negeri 2 Cot Girek, North Aceh.